Development of Discovery-Based Outdoor Learning Integrated with Papua Local Wisdom to Improve Cooperation and Understanding of the Biodiversity Concept of Students of Phase E of Sman Khas Papua - Evi Linda; Anna Rakhmawati; Paidi (Postgraduate, University of Mataram, 2025)
This study aims to develop a discovery-based outdoor learning model integrated with Papuan local wisdom to improve the collaboration skills and understanding of biodiversity concepts of phase E students at SMAN Khas Papua. The background of this study is based on the low context of science learning regarding the local environment and culture, even though Papua has very high ecological and cultural potential to be used as a learning resource. The method used is the Design-Based Research (DBR) Plomp model which consists of three stages: introduction, development/prototyping, and summative assessment. The results of expert validation show that the model and learning tools have very good validity values (Average Validator Agreement > 3.5). Practicality tests through observation and questionnaires on teachers and students show that the model is easy to implement and helps make learning meaningful. The effectiveness of the model is proven by a significant increase in student learning outcomes (t-test; p < 0.05) as well as the development of collaboration skills through outdoor learning. The integration of Papuan local wisdom, such as forest conservation practices and traditional medicine, encourages emotional engagement and contextual scientific understanding. This model also supports the implementation of the Independent Curriculum and the strengthening of the Pancasila Student Profile. This research makes an important contribution to the development of innovative and adaptive local culture-based science learning in the 3T context. Further, large-scale studies are needed to test the model's sustainability and replicability in various regions with similar characteristics.